Pengaruh Gaya Mengajar Komando Terhadap Kemampuan Servis Panjang Dalam Permainan Bulutangkis Pada Siswa SMP Negeri 1 Bitung - Muhammad Ridwan Eriandi; Bacilius Sukadana; Serli Ompi (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
The aim of the study was to determine the influence of the commando teaching style on the results of long serve in students of SMP Negeri 1 Bitung. Data Collection was carried out by direct measurement in the field. Measurement is done by measuring the exact length of the service to the specified target. Data processing is done by testing the analytical requirements that must be met, namely the normality test and homogeneity test. The results showed that there was an effect of the commando teaching style on the improvement of long serve results in badminton for student of SMP Negeri 1 Bitung.